1992
DOI: 10.1017/s0020818300033245
|View full text |Cite
|
Sign up to set email alerts
|

Interests, power, and multilateralism

Abstract: Multilateralism characterizes, to varying degrees, patterns of interaction among states and the formal organizations they construct. The utility of multilateral norms or organizations varies with the type of cooperation problem states confront. Thus, the functional logic of international cooperation leads to hypotheses about the conditions under which the institution of multilateralism may be a feasible and efficient solution, as in coordination problems, and those under which it will not, as in collaboration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
181
1
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(192 citation statements)
references
References 36 publications
0
181
1
10
Order By: Relevance
“…Previous results from these laboratories (Jain et al, 1996) have shown that when 7-O-methoxyacetyl-4-methyl-2H-l-benzopyran-2-one, (I), is subjected to a Fries (Martin, 1992) reaction under dry conditions using aluminium chloride as the Lewis acid, two new isomeric bis-coumarins, 8,St-methylenebis(7-hydroxy-4 -methyl-2H-l-benzopyran-2-one) and 6,8'-methylenebis(7-hydroxy-4-methyl-2H-1-benzopyran-2-one), are produced. This result was surprising because the simple rearrangement products, 7-hydroxy-8-methoxyacetyl-4-methyl-2H-1-benzopyran-2-one or 7-hydroxy-6-methoxyacetyl-4-methyl-2H-l-benzopyran-2-one, had been anticipated.…”
Section: Commentmentioning
confidence: 98%
“…Previous results from these laboratories (Jain et al, 1996) have shown that when 7-O-methoxyacetyl-4-methyl-2H-l-benzopyran-2-one, (I), is subjected to a Fries (Martin, 1992) reaction under dry conditions using aluminium chloride as the Lewis acid, two new isomeric bis-coumarins, 8,St-methylenebis(7-hydroxy-4 -methyl-2H-l-benzopyran-2-one) and 6,8'-methylenebis(7-hydroxy-4-methyl-2H-1-benzopyran-2-one), are produced. This result was surprising because the simple rearrangement products, 7-hydroxy-8-methoxyacetyl-4-methyl-2H-1-benzopyran-2-one or 7-hydroxy-6-methoxyacetyl-4-methyl-2H-l-benzopyran-2-one, had been anticipated.…”
Section: Commentmentioning
confidence: 98%
“…Liberal-institutionalists (LI) (e.g., Martin, 1992) claim that being part of a number of international organizations and/or regimes changes or modifies Great Powers' interests by making the very existence of those relationships a central issue in their agendas; this would severely constrain Great Powers' ability to force their preferences and perspectives upon others' less those relationships might be jeopardized (e.g., Keohane, 1984;Keohane, 1993) 1 . On the other hand, structuralrealists (SR) claim that security issues tower so high above all others that multilateral organizations or regimes will either adjust to international power asymmetries or will become irrelevant or disappear (e.g., Waltz, 1979Waltz, , 1993Waltz, , 2000Grieco 1993aGrieco , 1993bGrieco , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…This is refl ected in parallel changes in perspective and related semantic shifts. These changes have been traced by, among others, Lisa Martin and Beth Simmons, who point to specifi c historical events that have led to attendant changes in the research on international institutions (Martin 1992;Martin / Simmons 1998 In the Cold War period, a bipolar world system developed in which the United States was embedded as hegemon of the Western world. Hegemonic stability theory, while recognizing existing power asymmetries, emphasized the benefi ts a dominant state could derive from international institutions.…”
Section: The Impact Of Historical Developmentsmentioning
confidence: 99%
“…Cutting edge international relations work now dealt with the imbalances in the international power structure. Among liberal institutionalists, the new "buzzword" was multilateralism (see Keohane 1990;Ruggie 1993), and interest turned to the threat that an asymmetric international power structure poses to it (Martin 1992). Multilateralism is a narrower concept than governance; it focuses specifi cally on relations between states, while the concept of global governance refers to a variety of public as well as private actors.…”
Section: The Impact Of Geopolitical Contextmentioning
confidence: 99%
See 1 more Smart Citation